2021
DOI: 10.1002/ep.13762
|View full text |Cite
|
Sign up to set email alerts
|

Performance, environment, and cost‐benefit analysis of a split air conditioning unit usingHC‐290 andHCFC‐22

Abstract: A widely used hydrochlorofluorocarbon (HCFC) refrigerant HCFC-22 in the split air conditioner (AC) is being phased out in all countries under the Montreal Protocol.Propane (HC-290) is a favorable substitute for HCFC-22. The performance, environment impact and cost-benefit analysis of a split AC unit operated with HCFC-22 and HC-290 has been carried out experimentally under different test conditions prescribed by IS 1391. The results showed that the variation in system performance was more significant for HCFC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Lorentzen suggested that the use of natural refrigerants is a better solution. As a kind of natural refrigerants, hydrocarbons, such as propane (R290) and isobutane (R600a), are considered as substitutes for traditional hydrofluorocarbon (HFC) or hydrochlorofluorocarbon (HCFC) refrigerants due to the zero ODP and very low GWP. …”
Section: Introductionmentioning
confidence: 99%
“…Lorentzen suggested that the use of natural refrigerants is a better solution. As a kind of natural refrigerants, hydrocarbons, such as propane (R290) and isobutane (R600a), are considered as substitutes for traditional hydrofluorocarbon (HFC) or hydrochlorofluorocarbon (HCFC) refrigerants due to the zero ODP and very low GWP. …”
Section: Introductionmentioning
confidence: 99%